Three-dimensional microscopic comparison of wear behavior between immature and mature enamel: an in vitro study - Kanae Wada; Manhal Ijbara; Nesreen A. Salim; Junichiro Wada; Tsutomu Iwamoto (BMC, 2023)
Abstract Background Dental enamel, the hardest outermost layer of a human tooth, is subjected to occlusal forces throughout life during different oral function as talking, mastication etc. Due to this continuous stress, wear causes the loss of this protective shell. This study aimed to detect microscopic differences in enamel's wear behavior among different age groups of adolescents and adults. Aims and methods Enamel specimens from immature open-apex and mature closed-apex premolars were subjected to simulated occlusal wear of impact and sliding wear test ISWT. Upper and lower enamel specimens were made to come in contact under controlled conditions. The enamel specimens' surfaces were examined using different microscopes. The upper and lower specimens were subjected to the following tests; pre-test light microscopy examination, enamel specimens' preparation for ISWT, scanning laser confocal microscopy of upper specimens, three-dimensional (3D) colored laser microscope and a Profilometer imaging of the lower specimens. Results Wear characteristics, including wear areas, crater depths, and relation to enamel microstructures, differed among different age groups. Immature enamel from the upper specimens was more resistant to chipping than mature enamel with no statistically significant wear area difference. The immature enamel craters from the lower specimens were wider and deeper than those in the mature enamel; the wear areas in the mature enamel in the lower specimens were almost flat and smooth. The wear areas in the immature enamel in the lower specimens were significantly larger than those in the mature enamel. Conclusions Wear characteristics of the immature enamel are different from those of the mature enamel. Hence, it should be repaired using restorative materials with compatible wear properties.